AN INVESTIGATION ON THE FERMENTATIVE CHANGES DURING BAMBOO SHOOT PROCESSING TO THE PRODUCTION OF SOIBUM - S. GIRI SINGH (The Bioscan, 2015)
Succulent bamboo shoots of Bambusa nutan and Dendrocalamus latiflorus were separately processed into Soibum by natural lactic acid fermentation adopting a traditional method. During 28 days fermentation, pH dropped in both mashes by same value of 1.33, but accumulation of titratable acidity in the former mash was lower although its level of reducing sugar had been rapidly reduced. The processing was accompanied with the increase in the levels of titratable acidity, pyruvic acid, α-Ketoglutaric acid, diacetyl, acetoin, alcohol and esters by values of 1.00 - 1.15%; 1.40-1.54, 0.88-1.38, 172.67-372.65, 15.79-33.29, 51.18-142.66 and 58.34-65.55 in mg/100g respectively during the entire period. The intermittent levels for each of these entities in the two mashes were also varied widely in most of the cases. Better quality of Soibum mash of B. nutan could be related with possession of lower levels of titratable acidity, diacetyl, acetoin and higher level of esters. Based on the present findings some suggestions have been made for improvement of traditional methods of Soibum processing and its quality.